Outcomes of patients with opioid use disorders seen at the Groote Schuur Hospital Addictions Clinic from 2014 to 2020 - Kadenge, Betty (Department of Psychiatry and Mental Health, 2024)
BACKGROUND: The 2019 World Drug Report estimates an increased rate of non-medical use of opioids globally. A significant amount of this is attributable to the use of heroin. This rising trend is of particular concern in South Africa, a country which holds a background of high prevalence rates of blood borne infections such as HIV and Hepatitis C. Despite existing evidence for positive outcomes of Opioid Substitution Treatment (OST) in international and local studies, its use remains limited in South Africa, where medications suitable for use as OST are only listed in the Essential Medicines List for detox and not long-term maintenance treatment. METHODS: This study was a retrospective, descriptive study conducted at the Groote Schuur Hospital addictions clinic, a tertiary academic hospital in the Western Cape. Data was extracted from a total of 45 folders meeting inclusion criteria for this study and analysed using the SPSS software package. Descriptive statistics (frequencies, mean, and median) were used to examine the distribution of all socio-demographic, substance use, within-treatment, and treatment outcome variables. Chi-square tests were used to explore associations between sociodemographic, substance use, factors at baseline and the treatment outcomes of interest (abstinence and remission from OUD). For each outcome of interest, variables associated with the outcome at p<0.1 were entered into multiple logistic regression models. This purposeful method of selecting covariates to enter the models is widely used and recommended for researchers interested in identifying factors associated with an outcome and not just predicting the effects of a single covariate. The intention of these logistic regression analyses was to explore whether variables associated with the outcome of interest in bivariate analyses remained significantly associated with the outcome when adjusting for the presence of other variables associated with the outcome. RESULTS: The majority of participants in this study were male (53.3%), unemployed (84.4%), and did not attain more than 12 years of education (81%). The most common comorbid psychiatric condition in this study was major depressive disorder. Most participants in this sample were using heroin with a third of these participants injecting heroin. Comorbid SUD included tobacco (n=13, 30%) and stimulants (n=13, 29%) The use of OST overall held positive associations across all outcomes investigated in this study. CONCLUSION: This study highlights the complex interplay of sociodemographic, clinical and substance use factors of patients with opioid use disorders. It also highlights the benefits of maintenance OST and may add value to existing treatment services by identifying positive predictive factors for remission and abstinence. The authors of the study recommend replicating similar large-scale studies and continuing to advocate for inclusion of maintenance OST as part of integrated treatment of comorbid medical, psychiatric and substance use disorders, including tobacco use disorder in South Africa.